Formulation and process improvement for chili shrimp paste using sensory evaluation - Mohd Firus, Nadia Sarina; Mohd Adzahan, Noranizan; Sobhi, Babak; Abdul Karim, Muhammad Shahrim; Karim, Roselina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
This study was conducted to improve the formulation of chili shrimp paste (CSP) based on sensory evaluation in terms of acidity, source of acid and coarseness of chili paste and to improve the production process of CSP. The effectiveness of dimethyl dicarbonate (DMDC) as a microbial reduction agent was also evaluated. To produce CSP with different coarseness, a milling machine was used. Two types of preference test were conducted, i.e. ranking and hedonic. The preferred pH level was 4.0, the best acid source was kalamansi juice, and the most preferred coarseness for chili paste was when milling plates with a gap of 120 μm was used. DMDC has no effect on microbial reduction due to the presence of fat globules in CSP which hindered the inactivation action. Milling can substitute pounding as it is much faster and can produce a uniform CSP with higher volume.